Connecting - Helen Walker; Jan Buley; S. Rebecca Leigh; Christopher M. Bache; Bette B. Bauer; Rachel Forrester; Laurence Musgrove (Journal of the Assembly for Expanded Perspectives on Learning, 2011)
Connecting Helen Walker - Teaching/Seeing Jesus Jan Buley - The Realization S. Rebecca Leigh - Celebrating Ways of Learning Christopher M. Bache - The Opening Question Bette B. Bauer - Teaching as a Spiritual Practice Rachel Forrester - Appalachia Finally in the Spring Laurence Musgrove - Syllabus